Assessment of Trace Elements Concentration in Selected Vegetables from High and Low Cancer Prevalence Areas in Ondo State, Nigeria - Joshua O Ojo; Danjuma D Maza; Grace O Akinlade; Osualale P Taiwo (Physics Access)
This study investigates the potential link between cancer incidence and trace elements and heavy metals intake from locally grown vegetables in Ondo West and Ondo East Local Government Areas of Ondo Stae, Nigeria. It builds on a 2019 study by Adeola and colleagues, which identified a significantly higher cancer incidence in Ondo West compared to Ondo East, with rates three times higher. Five commonly consumed vegetables—Solanum macrocarpon, Talinum triangulare, Amaranthus hybridus, Telfairia occidentalis, and Vernonia amygdalina— were sampled from 47 locations across both regions. The samples were oven-dried, digested, and analyzed using atomic absorption spectroscopy (AAS) to determine the mean concentrations of essential trace elements (magnesium, manganese, and zinc) and toxic heavy metals (lead and cadmium). The estimated daily intake (EDI), daily intake (DI), and chronic daily intake (CDI) were calculated and used to assess the incremental lifetime cancer risk (ILCR), non-cancer hazard quotient (HQ), and non-cancer health index (HI). Contributions to the recommended daily intake of magnesium, manganese, and zinc through vegetable consumption were 12.65%, 40.8%, and 9.6%, respectively, in Ondo West, and 13.7%, 47.7%, and 10.58%, respectively, in Ondo East. The total non-cancer health indices were 0.90 and 0.92 for Ondo West and Ondo East, respectively, indicating no significant non-cancer health risks from consuming these vegetables. However, the ILCR values were calculated as 0.000293 for Ondo West and 0.000416 for Ondo East, exceeding the threshold of 1.0 × 10⁻⁵, suggesting a potential cancer risk. Despite this finding, the study could not account for the notably higher cancer prevalence in Ondo West.